2021
DOI: 10.3389/fonc.2021.687884
|View full text |Cite
|
Sign up to set email alerts
|

CT-Based Radiomics Signature With Machine Learning Predicts MYCN Amplification in Pediatric Abdominal Neuroblastoma

Abstract: PurposeMYCN amplification plays a critical role in defining high-risk subgroup of patients with neuroblastoma. We aimed to develop and validate the CT-based machine learning models for predicting MYCN amplification in pediatric abdominal neuroblastoma.MethodsA total of 172 patients with MYCN amplified (n = 47) and non-amplified (n = 125) were enrolled. The cohort was randomly stratified sampling into training and testing groups. Clinicopathological parameters and radiographic features were selected to construc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 30 publications
2
29
0
Order By: Relevance
“…Most studies have shown that radiomics features of CECT images are correlated with the degree of malignancy of neuroblastomas. 17,29 In this study, the most important radiomics features mainly included shape and texture features. The shape features included sphericity, maximum 2D diameter slice, flatness, maximum 2D diameter column, and surface area.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have shown that radiomics features of CECT images are correlated with the degree of malignancy of neuroblastomas. 17,29 In this study, the most important radiomics features mainly included shape and texture features. The shape features included sphericity, maximum 2D diameter slice, flatness, maximum 2D diameter column, and surface area.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported radiomics potential role to predict molecular biomarkers in neuroblastoma, including MYCN in neuroblastoma by CT-based radiomics signature [ 8 , 25 ], tumor-associated macrophages by contrast-enhanced CT [ 26 ]. Moreover, some studies demonstrated that combining radiomics features with clinical characteristics can provide incremental predictive value for gene mutant status and expression.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the progress in computer-assisted technology and image analysis, accurate evaluation of MKI status still faced some challenges. Meanwhile, as an invasive approach, the traditional biopsy may result in various complications [ 8 ], therefore, another non-invasive approach is needed to efficiently describe the status of MKI.…”
Section: Introductionmentioning
confidence: 99%
“…Whether IDRF obtained from radiological images is associated with MYCN ampli cation also requires further investigation. The emergence of radiogenomics may provide a promising method for the noninvasive characterization and prediction of molecular biomarkers [26,27].…”
Section: Discussionmentioning
confidence: 99%